Toxoplasmosis can be a sexually transmitted infection with serious clinical consequences. Not all routes of infection are created equal - Flegr, J; Klapilová, K; Kaňková, S (Medical hypotheses, 2014)
Toxoplasma gondii infects about 30% of the human population. Common sources of infection are oocysts in cat faeces contaminating drinking water or unwashed vegetables, undercooked meat containing tissue cysts, and organ transplants from infected donors containing tissue cysts. However, very often, it is not possible to identify any potential source of infection in mothers of children with congenital toxoplasmosis. Here we present a hypothesis suggesting that toxoplasmosis is transmitted from infected men to noninfected women during unprotected sexual intercourse, which can result in the most serious form of disease, congenital toxoplasmosis. Arguments for the hypothesis: (1) Toxoplasma tachyzoites are present in the seminal fluid and tissue of the testes of various animals including humans. In some species infection of females by artificial insemination with semen from infected males has been observed. (2) Up to two thirds of Toxoplasma infections in pregnant women cannot be explained by the known risk factors. (3) Prevalence of toxoplasmosis in women in child-bearing age covaries with the incidence of sexually transmitted diseases in particular countries. (4) In some countries, an increased incidence of toxoplasmosis has been reported in women (but not men) aged 25-35 years. This second peak of infection could be associated with women having regular unprotected sex after marriage. (5) Toxoplasmosis triggers schizophrenia in predisposed subjects. Onset of schizophrenia is about 2-3 years earlier in men than in women. However, this difference in the onset can be found only between Toxoplasma-infected patients. The increased onset of schizophrenia in infected women could be associated with the already mentioned second peak of toxoplasmosis incidence. (6) The prevalence of toxoplasmosis decreases in developed countries in last 20 years. This trend could be a result of decrease in promiscuity and increase in safe sex practices, both associated with the AIDS pandemics. (7) In women, probability of being Toxoplasma-infected correlates positively with the amount of unprotected sex with the child's father before the conception. Evidence against the hypothesis: Questionnaire study showed negative association between Toxoplasma infection and the number of earlier partners with whom the woman had unprotected sex. If our hypothesis turns out to be true, then sexual route of transmission, even if rare, could be responsible for a large part of cases of congenital toxoplasmosis. Women should be warned that having unprotected sex with men of positive or unknown toxoplasmosis status should be avoided during pregnancy.
Keywords: Toxoplasma; Male; sexuálně přenosné nemoci; Risk Factors; kočky; Unsafe Sex; Schizophrenia; Pregnancy; těhotenství; Adult; transplantace orgánů; dospělí; toxoplazmóza; mužské pohlaví; Organ Transplantation; průzkumy a dotazníky; Sexual Partners; sperma; Semen; Animals; lidé; Toxoplasmosis; ženské pohlaví; Humans; rizikový sex; zvířata; Sexual Behavior; schizofrenie; rizikové faktory; sexuální chování; sexuální partneři; Sexually Transmitted Diseases; Female; Surveys and Questionnaires; Cats